2021
DOI: 10.26434/chemrxiv.14459319.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemical Compositions in Modified Salinity Waterflooding of Carbonate Reservoirs -- Experiment

Abstract: <br>Modified or low-salinity waterflooding of carbonate oil reservoirs is of considerable economic interest because of potentially inexpensive incremental oil<br>production. The injected modified brine changes the surface chemistry of the carbonate rock and crude oil interfaces and detaches some adhered crude oil.<br>Composition design of the modified brine to enhance oil recovery is determined by labor-intensive trial-and-error laboratory corefloods. Unfortunately, limestone,<br>which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“… 5 9 However, despite intense research in this field, the underlying mechanisms that lead to improved oil recovery are still debated. 10 21 Moreover, the complex rheology of the interfacial films dictates the stability of oil/water emulsions, with implications in oil transport, processing, and final quality. 22 , 23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 9 However, despite intense research in this field, the underlying mechanisms that lead to improved oil recovery are still debated. 10 21 Moreover, the complex rheology of the interfacial films dictates the stability of oil/water emulsions, with implications in oil transport, processing, and final quality. 22 , 23 …”
Section: Introductionmentioning
confidence: 99%
“…In particular, the interfacial properties of crude oil have received significant attention over the past decades because of their relevance to oil recovery, transport, and processing. For example, most oil extraction processes are based on injecting water-based liquids, called brines, into the porous oil reservoir. The efficiency of this process, known as waterflooding, is generally understood as an interplay between viscous and interfacial forces, and it has been shown that it can be enhanced by tuning the chemical composition of the brine, for example, by reducing its salinity or by selectively increasing the concentration of certain divalent ionic species. However, despite intense research in this field, the underlying mechanisms that lead to improved oil recovery are still debated. Moreover, the complex rheology of the interfacial films dictates the stability of oil/water emulsions, with implications in oil transport, processing, and final quality. , …”
Section: Introductionmentioning
confidence: 99%
“…The system becomes even more complex when chemicals such as surfactant and polymer are included, which interact with other aqueous species and can adsorb to the calcite surface. A one-dimensional (1D) reactive transport model that can describe compositional changes of brines containing Na + and Cl – during flow through calcite was recently developed by Yutkin et al and validated with core flooding experiments. , In their model, both calcite and clay mineral phases are included to model surface complexation and ion exchange, respectively. The anionic surface sites are neutralized through 2:1 Ca 2+ /Na + mass-action ion exchange, while a diffuse layer is absent due to the collapse of the EDL on the outer Helmholtz plane.…”
Section: Introductionmentioning
confidence: 99%